EFFECT OF DROUGHT STRESS AND ADDITION OF ARBUSCULA MYCORRHIZAL FUNGI (AMF) ON GROWTH AND PRODUCTIVITY OF TROPICAL GRASSES (Chloris gayana, Paspalum dilatatum, and Paspalum notatum) - Pebriansyah A; - Karti; - P.D.M.H; - A.T (Udayana University)
Grasses productivity is affected by soil water availability. Arbuscular Mycorrhizal Fungi (AMF) was innoculated to support plant to overcome drought stress during its growth. The aim of this study was to understand the role of Arbuscular Mycorrhizal Fungi (AMF) to support growth and the production of grasses in drought stress condition. Three species of tropical grasses : Chloris gayana, Paspalum notatum, and Paspalum dilatatum were used. The research used completely randomized design with 4 treatments consisting of M0S0 = without AMF and daily watering, M0S1 = without AMF and without watering; M1S0 = with mycorrhiza and daily watering; M1S1 = with AMF and without watering. and 5 replications. The four treatments research were as follows; Each type of grasses were obsereved in a separate study. The result showed that AMF played significant role in improving growth and root dry weight biomass of Chloris gayana in drought condition. Paspalum notatum is the most adaptive grass in the drought condition. Chloris gayana has the growth and a better production than Paspalum dilatatum.